Estratégia de regulação de tensão em redes de distribuição com geração distribuída fotovoltaica assistida por infraestrutura integrada de telecomunicações - Leonardo Henrique de Melo Leite (2016)
Massive penetration of Distributed Generation Photovoltaic Systems - DGPV - connected to the power distribution grid through electronic inverters can contribute, in an aggregate service scenario, to the performance of several power system control functions, notably in voltage regulation along a distribution feeder. In this context, the supervision and control of these generating units through a standardized, flexible and capillary communication infrastructure become a key factor in enabling large-scale integration. Present voltage regulation methods adopted in distribution grids using the potential of DGPV units are based on the local interaction of each source with the power grid, without exploiting the potential benefits of a wide integration among them. This work proposes an optimization method for voltage regulation in distribution grids with DGPV, focused on reactive power flow control, based on a communication architecture model that coordinates the interaction among the inverters of DGPV units. This architecture enables each distributed source of different manufacturers to perform in accordance with its operational characteristics and location, while dynamically coordinated by a Distributed Generation Management System. The proposed communication infrastructure is based on the connectivity and interoperability requirements established by the Smart Grid IEEE 2030 reference model and international standard IEC 61850. A sensitivity analysis regarding the performance of voltage regulation in distribution grids with DGPV, based on a co-simulation between energy infrastructure and communication network, shows the effectiveness of the proposed optimization method. Voltage regulation in steady state and grid reconfiguration action (self-healing) scenarios are performed through a simulation environment upon a special simulation arrangement using PSCAD e MatLab platforms.